Information users ’ preference on the use of print and Electronic Resources in Selected Universities in Tanzania: A Survey - Samzugi, Athumani S (University of Dar es Salaam Library Journal, 2020)
This paper is based on a study that examined information users ' preference on use of print and electronic resources in selected universities in Tanzania. A survey method was used as the research design to facilitate the collection of data from the three sampled universities in Tanzania, namely the University of Dar es Salaam (UDSM), the Open University of Tanzania (OUT) and Tumaini University-Dar es Salaam College (TUDARco). Purposive sampling technique was used to select respondents, comprising undergraduate and post-graduate students, academic and research staff. Empirical data for the study were collected using a questionnaire survey and interview guide. Out of 350 administered questionnaires, 327 were successfully completed and used for the study, yielding a 93.4 Percent return rate. The study found out that print resources are more preferred than electronic ones. These findings are not in congruency with the popular assumption that the ready availability of online resources has supplanted print resources. However, one significant finding in this study is that e-resources popularity has started to gain ground across the three universities under review. The respondents suggested fostering the use of both print and electronic resources in universities, for wider access of knowledge, particularly in the resource-limited contexts prevailing in Tanzania. Based on the findings, the study concluded that a hybrid collection is the panacea to optimising resources as it provides users with more access choices between the two formats.